Monitoring the internal and external loads of young team handball players during competition - Maric, D.; Gilic, B.; Foretic, N. (SportMont, 2021)
This study aimed to examine the internal- and external-training-load (ITL and ETL, respectively) during a match of young handball players. Field testing included heart-rate monitoring (memory belt, Suunto) as a marker of ITL and accelerometry (motion-biosensor, Actical Respironcis, Philips) as a marker of ETL. Time motion analysis data were obtained by recording the player`s game activities and later analysed with the Matlab software package. T-test and Pearson-product-moment correlation coefficient were used to examine the differences and the relationship between variables collected in the study. The t-test analysis did not show significant differences between the total distance covered (2216.42-2135.42 m), steps conducted (1829.25-1829.83 steps), steps per minute (91.46-91.49 steps/min), energy expenditure (92.24-90.87 METS), time spent in higher intensity zones calculated by motion biosensor (13.08-12.75 minutes), training- load calculated by Edwards TRIMP method (91.54-88.56 scores) in the first and in the second half of the match. Physical activity variables show no significant correlations with the data assessed by heart rate monitors. Similar results in monitored training-load variables in the first and second halves are connected with the game intensity, which was consistent throughout the match. The lack of correlations between ITL and ETL variables indicates that accelerometry is not suitable for the assessment of metabolic training load in intermittent activities, such as handball. ITL measures used in this study are more suitable for controlling load during training and competition, while the ETL parameters used are more appropriate for better understanding players activity in periods in which the players do not train; other activities can influence players fatigue and training and competition performance.